Israelite or Universal Horizon: Zephaniah 3.8–10 in the Hebrew and Greek Bibles - Schenker, Adrian (The Bible translator, 2013)
Zephaniah 3.8-10 is translated in current English Bibles in different ways. The translations either follow the Hebrew Masoretic text or the Greek or a mixture of both, or they introduce emendations, whether explicitly or without note. Unless translators understand this difficult textual situation they are at a loss how to translate. Emendations certainly should be avoided. The Masoretic text and the Old Greek have different meanings. These two meanings are explained and compared. The probable reason for the divergence is given, and the more original and the later text are determined. Thus translators are in a position to choose one of the two existing textual forms, not by guessing but by understanding.